Perbandingan Double Moving Average dan Double Exponential Smoothing untuk Peramalan Jumlah Kedatangan Wisatawan Mancanegara di Bandara Ngurah Rai - Cinthia Vairra Hudiyanti; Fitra Abdurrachman Bachtiar; Budi Darma Setiawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Every year the number of international tourist arrivals in Bali always increases (BPS, Statistics Indonesia). Increasing the number of international tourist arrivals will have an impact on the availability of facilities, infrastructure, and services for the airport or Angkasa Pura I. Many things affect foreign arrivals, resulting in the need forecasting the number of foreign arrivals whose results can be used by Angkasa Pura I as the airport manager and local government to improve services. This research forecasting is done using Double Moving Average and Double Exponential Smoothing. Accuracy calculation is done by using Mean Absoulte Percentage Error (MAPE). The data used are 120 data, from January 2008 to December 2017, and obtained from the official website of Statistics Indonesia. From this study testing in 2017 found the best time order value for the Double Moving Average is 2 and Double Exponential Smoothing with parameter ð›¼ = 0.4. From these parameter values, the MAPE Double Moving Average value is 10,522 and the MAPE Double Exponential Smoothing value is 3,355. At Double Exponential Smoothing has a value below 10, it is said to be very good, while the Double Moving Average with a value above 10 is said to be good. It can be concluded that Double Exponential Smoothing has better accuracy than Double Moving Average in forecasting the number of arrivals of foreign tourists at Ngurah Rai Airport.